Efficient data dissemination protocols for V2X communication networks - Gao, Yumeng (2019)
With the rapid development of intelligent transportation system (ITS) technology and applications, the real-time wireless connectivity of moving vehicles has attracted increasing attention in the academia and industries. Relying on vehicle-to-everything (V2X) communication, vehicles are enabled to communicate with vehicles directly, as well as with roadside infrastructures. V2X communication is able to support a variety of applications to address road safety concern and support commercial or regulatory ITS services. Confronted by dynamic vehicular environment and stringent latency requirements, the design of efficient V2X communication protocols are of great relevance. In this thesis, we aim to design efficient data dissemination schemes for a number of realistic V2X use-cases. To this end, we utilize techniques such as network coding and Markov chain modeling, and focus on media access control (MAC) layer enhancement and scheduling optimization.